2021
DOI: 10.1097/ruq.0000000000000583
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a Predictive Nomogram Based on Ultrasound for Lymph Node Metastasis of Papillary Thyroid Carcinoma in the Cervical Central Region

Abstract: To establish and validate a nomogram for predicting lymph node metastasis (LNM) of papillary thyroid carcinoma (PTC) in the cervical central region. This retrospective study included 287 PTC patients with 309 nodules treated from December 2018 to May 2020 at our hospital. The cohort was divided randomly into a training set and a testing set according to a 7:3 ratio. The training set contained 216 nodules, and the testing set contained 93 nodules. The nomogram was developed using the training set, and the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Nomograms, created by combining selected target variables, provide a clinical prediction model in a graphical manner that can be used to predict breast lesion diagnoses and prognoses for individual management. [36][37][38] In this study, the Clin + CUS model nomogram incorporating patient age and information on lesion size, peripheral hyperechoic halo, and BI-RADS category showed only moderate diagnostic performance in both the training and validation cohorts (AUC = 0.851, 0.863, respectively). Therefore, further approach for improving the diagnostic performance of CUS is advocated.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Nomograms, created by combining selected target variables, provide a clinical prediction model in a graphical manner that can be used to predict breast lesion diagnoses and prognoses for individual management. [36][37][38] In this study, the Clin + CUS model nomogram incorporating patient age and information on lesion size, peripheral hyperechoic halo, and BI-RADS category showed only moderate diagnostic performance in both the training and validation cohorts (AUC = 0.851, 0.863, respectively). Therefore, further approach for improving the diagnostic performance of CUS is advocated.…”
Section: Discussionmentioning
confidence: 67%
“…Although clinical and CUS features of breast lesions can provide some discrimination value, only when they are combined can they be used to accurately assess whole lesions and facilitate precision medicine. Nomograms, created by combining selected target variables, provide a clinical prediction model in a graphical manner that can be used to predict breast lesion diagnoses and prognoses for individual management 36–38 . In this study, the Clin + CUS model nomogram incorporating patient age and information on lesion size, peripheral hyperechoic halo, and BI-RADS category showed only moderate diagnostic performance in both the training and validation cohorts (AUC = 0.851, 0.863, respectively).…”
Section: Discussionmentioning
confidence: 77%
“…Shen et al. ( 12 ) identified gender (male), multifocality, maximum lesion diameter, and American College of Radiology Thyroid Imaging Reporting & Data System (ACR TI-RADS) score as independent risk factors for CLNM. Kim et al.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Mao et al (11) identified age (<45 years old), gender (male), multifocality, tumor size (>1 cm), and thyroid extracapsular invasion as factors that increase the risk of lymph node metastasis in PTC patients. Shen et al (12) identified gender (male), multifocality, maximum lesion diameter, and American College of Radiology Thyroid Imaging Reporting & Data System (ACR TI-RADS) score as independent risk factors for CLNM. Kim et al (13) concluded that Hashimoto's thyroiditis (HT) and PTC tend to occur at the same time and HT is known to increase the risk of PTC, but HT may also attenuate tumor aggressiveness and metastasis.…”
Section: Introductionmentioning
confidence: 99%